DEIKSIS DALAM FILM GOD’S NOT DEAD KARYA HAROLD CRONK - Tumoka, Edwin Edwar; Pelealu, Hetty; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT This research entitled